Remarks on the genus Homogryllacris Liu, 2007 (Orthoptera: Gryllacrididae: Gryllacridinae) - Shi, Fu-Ming; Guo, Li-Ying; Bian, Xun (Zootaxa, 2012)
Four new species of the genus Homogryllacris Liu, 2007 are described, H. anelytra sp. nov., H. ascenda sp. nov., H. brevispina sp. nov. and H. yunnana sp. nov. A key to the species and the distributional data of the genus are provided. The all specimens recorded here are deposited in the Museum of Hebei University.